2010
DOI: 10.1113/expphysiol.2009.049965
|View full text |Cite
|
Sign up to set email alerts
|

Infarction‐induced cytokines cause local depletion of tyrosine hydroxylase in cardiac sympathetic nerves

Abstract: Myocardial infarction causes a heterogeneity of noradrenergic transmission that contributes to the development of ventricular arrhythmias and sudden cardiac death. Ischaemia-induced alterations in sympathetic transmission include regional variations in cardiac noradrenaline (NA) and in tyrosine hydroxylase, the rate-limiting enzyme in NA synthesis. Inflammatory cytokines that act through gp130 are elevated in the heart after myocardial infarction. These cytokines decrease expression of tyrosine hydroxylase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 44 publications
5
37
0
Order By: Relevance
“…Increases in sympathetic outflow have been documented with chronic heart disease (7,18,24). Changes in sympathetic innervation of the heart following MI show regional variation (16,22), but in the atrial regions, where the neurons for this study are located, studies showed either no change in NE innervation or an upregulation of sympathetic innervations (16,21). Even though the tissue damage produced by the MI is small and distant from the cardiac plexus studied, as in previous studies (13), this injury is sufficient to produce functional changes in the intrinsic neurons.…”
Section: Discussionmentioning
confidence: 67%
“…Increases in sympathetic outflow have been documented with chronic heart disease (7,18,24). Changes in sympathetic innervation of the heart following MI show regional variation (16,22), but in the atrial regions, where the neurons for this study are located, studies showed either no change in NE innervation or an upregulation of sympathetic innervations (16,21). Even though the tissue damage produced by the MI is small and distant from the cardiac plexus studied, as in previous studies (13), this injury is sufficient to produce functional changes in the intrinsic neurons.…”
Section: Discussionmentioning
confidence: 67%
“…Heart rate, LV end-diastolic pressure, and mean arterial pressure were elevated in animals with a previous MI compared with those without previous MI at baseline. The elevated heart rate and mean arterial pressure were likely due to increased neurohormonal stimulation, specifically from efferent activation (28). The mean pulse pressure, which is proportional to forward stroke volume, was not different between pigs with previous MI and those without previous MI at baseline.…”
Section: Methodsmentioning
confidence: 77%
“…Nuclei in the stellate ganglion modify the synthesis of sympathetic neurotransmitters under the influence of humoral factors derived from heart. For example, cardiac hypertrophic factors such as angiotensin II, 107 ET-1, 108 leukemia inhibitory factor (LIF), 24 NGF, 38,83,85 , other growth factors, 109 and cytokines 110 are augmented in failing heart, influencing sympathetic activity, function, plasticity, and phenotype. Complex crosstalk among these neurohumoral factors is thus believed to modulate cardiac sympathetic activation and the pathology of heart failure.…”
Section: Sympathetic Dysfunction In Heart Failurementioning
confidence: 99%